The deformation record of olivine in mylonitic peridotites from the Finero Complex, Ivrea Zone: Separate deformation cycles during exhumation. Issue 12 (23rd December 2015) - Matysiak, Agnes K.; Trepmann, Claudia A.
Abstract: Mylonitic peridotites from the Finero complex are investigated to detect characteristic olivine microfabrics that can resolve separate deformation cycles at different metamorphic conditions. The heterogeneous olivine microstructures are characterized by deformed porphyroclasts surrounded by varying amounts of recrystallized grains. A well‐developed but only locally preserved foam structure is present in recrystallized grain aggregates. This indicates an early stage of dynamic recrystallization and subsequent recovery and recrystallization at quasi‐static stress conditions, where the strain energy was reduced such that a reduction in surface energy controlled grain boundary migration. Ultramylonites record a renewed stage of localized deformation and recrystallization by a second generation of recrystallized grains that do not show a foam structure. This second generation of recrystallized grains as well as sutured grain and kink band boundaries of porphyroclasts indicate that these microstructures developed during a stage of localized deformation after development of the foam structure. The heterogeneity of the microfabrics is interpreted to represent several (at least two) cycles of localized deformation separated by a marked hiatus with quasi‐static recrystallization and recovery and eventually grain growth. The second deformation cycle did not only result in reactivation of preexisting shear zones but instead also locally affected the host rock that was not deformed in the first stage. Such stress cycles can result from sudden increases in differential stress imposed by seismic events, i.e., high stress‐loading rates, during exhumation of the Finero complex. Key Points: Mylonitic peridotites from the Finero complex Detection of characteristic overprinting microfabrics due to shear zone reactivation Resolution of different deformation cycles at different metamorphic conditions